Body composition changes over a collegiate playing career in NCAA Division I women's soccer players - Tinsley, G. M.; Meyer, M. K.; Ptak, S. M.; Yu, D.; Provost, J. A.; Hansen, N. J.; Carbuhn, A. F. (The Journal of Strength and Conditioning Research, 2025)
Although body composition is known to influence success in organized sport, the longitudinal body composition changes produced by sport specialization are not well characterized for women's soccer. To address this need, this study reports the body composition changes of NCAA Division I women's soccer players over their entire collegiate playing career. Serial dual-energy x-ray absorptiometry (DXA) scans were performed throughout players' involvement in collegiate women's soccer. Analyses of all players with multiple DXA scans (n = 80) and players with =3 years of DXA data (n = 17) were performed using linear mixed-effects models that included effects of time, playing position, game minutes, and interactions. In all athletes (n = 80; 2.1 ± 1.2 years of participation), significant increases in bone mass (1.4%), total lean mass (1.7%), and fat-free mass index (0.3 kg·m-2) occurred. These changes coincided with increased arm and leg bone mass, increased lean mass in all regions, and decreased body fat percentage and leg fat mass. In athletes with =3 years of collegiate data (n = 17; 3.5 ± 0.4 years of participation), larger increases in bone mass (3.0%), bone mineral density (2.2%), total lean mass (2.5%), fat-free mass index (0.4 kg·m-2), and segmental bone and lean mass were observed. Larger decreases in body fat percentage and leg fat mass were also noted. Although playing position was related to body composition characteristics, changes in outcomes were generally unrelated to position or game minutes. In summary, beneficial changes in multiple aspects of body composition were observed over years of participation in a collegiate women's soccer program.